2020
DOI: 10.7150/ijbs.48169
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1/FOXO3a axis plays an important role in the prevention of mandibular bone loss induced by 1,25(OH)2D deficiency

Abstract: It has been reported that 1,25 dihydroxyvitamin D [1,25(OH) 2 D] deficiency leads to the loss of mandibular bone, however the mechanism is unclear. We investigated whether the Sirt1/FOXO3a signaling pathway is involved in this process. Using a 1,25(OH) 2 D deficiency model induced by genetic deletion in mice of 25-hydroxyvitamin D-1α hydroxylase [1α(OH)ase -/- mice]. We first documented a sharp reduction of expression levels of Sirt1 in the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 50 publications
1
19
1
Order By: Relevance
“…Moreover, our results also showed that SIRT1 inhibition stimulated BM-MSCs’ cellular senescence, in agreement with previous studies evidencing SIRT1′s contribution to the prevention of MSCs’ senescence [ 42 , 65 , 66 , 67 ]. However, our results did not confirm the findings showing that vitamin-D3-mediated inhibition of senescence involves SIRT1 activation as it does in endothelial cells [ 68 , 69 ] and human-mandible-derived BM-MSCs [ 43 ]. Specifically, even in the presence of EX-527, VD3 led to the significant inhibition of BM-MSC senescence, indicating that VD3 exerted its anti-senescence effects in BM-MSCs via activation of other signaling pathways, which should be clarified in future studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Moreover, our results also showed that SIRT1 inhibition stimulated BM-MSCs’ cellular senescence, in agreement with previous studies evidencing SIRT1′s contribution to the prevention of MSCs’ senescence [ 42 , 65 , 66 , 67 ]. However, our results did not confirm the findings showing that vitamin-D3-mediated inhibition of senescence involves SIRT1 activation as it does in endothelial cells [ 68 , 69 ] and human-mandible-derived BM-MSCs [ 43 ]. Specifically, even in the presence of EX-527, VD3 led to the significant inhibition of BM-MSC senescence, indicating that VD3 exerted its anti-senescence effects in BM-MSCs via activation of other signaling pathways, which should be clarified in future studies.…”
Section: Discussioncontrasting
confidence: 99%
“…During the past decade, many studies have indicated an important role of SIRT1 signaling in MSC self-renewal, demonstrating its protective effects against DNA damage, reactive oxygen species, and various inflammatory and apoptotic stimuli [ 22 ]. Moreover, SIRT1 has been implicated in the promotion of murine and human BM-MSCs’ proliferation, and its role in bone homeostasis is generally well documented [ 37 , 42 , 43 , 44 ]. It has been also shown that vitamin D3 exerts its effects on MSCs by increasing SIRT1 expression via VDR-mediated transcription [ 43 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dental volume, reparative dentin volume, and dentin sialoprotein immunopositive areas were also reduced in 1α(OH)ase −/− mice, ( 37 ) and in the mandibles of 1α(OH)ase −/− mice, the cortical thickness, dental alveolar bone volume, and osteoblast number were also all decreased significantly, with accelerated alveolar bone loss. ( 38 ) The SIRT1/FOXO3a signaling axis appears to play an important role in the prevention of mandibular bone loss by 1,25(OH) 2 D. ( 39 )…”
Section: Calcitriol and Skeletal Homeostasismentioning
confidence: 99%
“…The dental volume, reparative dentin volume, and dentin sialoprotein immunopositive areas were also reduced in 1α(OH)ase −/− mice, (37) and in the mandibles of 1α(OH)ase −/− mice, the cortical thickness, dental alveolar bone volume, and osteoblast number were also all decreased significantly, with accelerated alveolar bone loss. (38) The SIRT1/FOXO3a signaling axis appears to play an important role in the prevention of mandibular bone loss by 1,25(OH) 2 D. (39) Effects on skeletal aging Bone mineral density, bone volume, Cyp27b1 renal protein expression, and circulating 1,25(OH) 2 D all decrease progressively with age in haploinsufficient 1α(OH)ase +/− mice, and Cyp27b1 gene haploinsufficiency accelerated age-related bone loss and an osteoporotic phenotype, accompanied by declining osteoblastic bone formation and increasing osteoclastic bone resorption. (40) The INK4a/ARF locus encodes the INK4 family of cyclindependent kinase inhibitors, including p16 INK4a , and a tumor suppressor p19/p14 ARF .…”
Section: Calcitriol and Teethmentioning
confidence: 99%